Effect of Type IIB von Willebrand Disease Mutation Arg(545)Cys on Platelet Glycoprotein Ib Binding – Studies with Recombinant von Willebrand Factor - Inbal, Aida; Kornbrot, Nurit; Harrison, Paul; Randi, Anna M; Sadler, J Evan (Thrombosis and Haemostasis, 1993)
Type IIB von Willebrand disease (vWD) is characterized by a selective loss of high molecular weight von Willebrand factor (vWF) multimers in plasma due to their abnormally enhanced reactivity with platelets. Several missense mutations in the platelet glycoprotein lb (GPIb) binding domain of vWF were recently characterized that cause type IIB vWD. The effect of type IIB mutation Arg(545)Cys on vWF binding to platelet GPIb was studied using recombinant wild type (rvWFWT) and mutant rvWFR545C expressed in COS-7 cells. In the absence of ristocetin, 50% of rvWFR545C bound spontaneously to platelet GPIb and the binding increased to 70% in the presence of 0.2 mg/ml ristocetin; rvWFWT did not bind significantly under either condition. Botrocetin-induced binding of rvWFR545C was only slightly increased compared to rvWFWT. These data demonstrate that the Arg(545)Cys mutation increases the affinity of vWF for GPIb, resulting in the characteristic gain-of-function type IIB vWD phenotype.